Pengaruh Penggunaan Model Problem Based Learning (PBL) Terhadap Perilaku Prososial dan Motivasi Belajar IPS di Kelas V SD Gugus IX Kota Bengkulu - Febby Intan Permata Sari; Badeni; Endang Widi Winarni (UNIB Press, 2024)
This research aims to determine the effect of using the problem based model (PBL) on prosocial behavior and social studies learning motivation in class V of SD Gugus IX Bengkulu City. This type of research is quantitative research. The research method used is quasi experimental design with the type of design